027. Successful Management of Penetrating Thoracic Injury With Impaled Object: A Case Report - Affan, M. Abror; Raz, Hashfi Fauzan (JBN (Jurnal Bedah Nasional), 2024)
Background : Penetrating thoracic injuries with impaled objects are rare but potentially life-threatening emergencies that require immediate medical intervention. These injuries pose significant challenges due to the risk of pneumothorax, hemothorax, and lung laceration. Prompt diagnosis and surgical management are essential to prevent severe complications. Case : A 28-year-old male was admitted to Adam Malik Hospital with a chief complaint of shortness of breath following an accident where a foreign object impaled his right chest. The injury occurred while he was repairing his motorcycle, and an explosion caused the object to penetrate his chest. The patient reported continuous right chest pain, worsened by breathing. On examination, he was alert with stable hemodynamics (BP: 130/70 mmHg, HR: 98 bpm, SpO2: 99% on 10L NRM), and a penetrating wound of 5x2x3 cm was observed in the right chest. Chest X-ray and clinical assessment confirmed a diagnosis of hemopneumothorax with an impaled object. Emergency thoracotomy revealed 800cc of hemorrhagic fluid, lung laceration, and a foreign body penetrating the right lung's superior and medial segments. The foreign body was removed, the lung was sutured, and a thoracic drain was placed. Conclusion: This case highlights the importance of timely surgical intervention in penetrating thoracic injuries. Hemodynamic stability and appropriate surgical techniques led to a successful outcome in this patient, demonstrating the effectiveness of rapid, multidisciplinary management in emergency thoracotomy.